Pancacuriga as a Tool for Analyzing Texts and Social Phenomena - Budi Setiawan Gardapandawa (Universitas Pasundan, 2026)
Semiotics and discourse analysis serve as intellectual tools for exploring meaning beneath the surface, even unearthing the meaning behind the meaning. Meanwhile, Pancacuriga, also a